Efficacy of Different Feed Additives on In Vitro Degradability of Maize Hay and Bajra Straw Based Total Mixed Ration - Patel; Garg, Deen Dayal; K Sharma, Arun; H Savsani, Harish; A Chavda, Jignesh; M Kalam, Sanket (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was conducted to investigate the efficacy of different feed additives (Monensin T1, cellulase 10,00,000 IU/g T2, xylanase 1,50,000 IU/g T3, chitosan T4, sodium bicarbonate T5, magnesium oxide T6, combination of sodium bicarbonate + magnesium oxide T7 and combination of cellulase + xylanase T8 added at the level of 30 mg/kg, 0.5%, 0.5%, 1%, 1%, 1%, 0.5% (Each) and 0.5% (Each) on DM basis, respectively) on in vitro degradability of total mixed ration prepared by taking maize hay, bajra straw and concentrate in the ratio of 30:30:40 and used as substrates for experiment. Rumen liquor was collected from two adult Surti goats 2 h post-feeding. Statistical analysis revealed that IVDMD (%), IVOMD (%), IVNDFD (%), IVADFD (%), TDOMR (%), IVTGP (mL/200 mg), SCFAs (mMol/200 mg), ME (MJ/kg) and NE (MJ/kg) were significantly (p<0.01) increased in TMR supplemented with combination of cellulase and xylanase (67.32±1.01, 69.97±1.29, 56.23±0.36, 53.01±1.64, 64.13±0.42, 32.92 ±0.62, 0.75±0.007, 6.16±0.09 and 3.74±0.05 respectively). This was followed by TMR supplemented with cellulase, xylanase and chitosan alone, which also had significantly (p<0.01) higher values of all these components as compared to control (52.34±0.31, 54.92±0.50, 41.48±1.63, 38.64±0.53, 49.41±1.20, 22.08±0.56, 0.49±0.01, 4.58±0.08 and 2.70±0.05, respectively). Hence a combination of cellulase and xylanase is recommended as feed additive in maize hay, bajra straw and concentrate based TMR.